KONSEP PSYCHOLOGICAL WELL-BEING SERTA IMPLIKASINYA DALAM BIMBINGAN DAN KONSELING - Irma Yuliani (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
The purpose of this article is to explain psychological well-being concept to be applied in guidance and counseling. Guidance and counseling service to improve psychological well-being could be a way to help people achieve their optimum individual potention in every phase of development, so they clould live with happy and prosperous. Feeling happiness, fun, and satisfaction are the outcome of psychological well-being. Therefore, psychological well-being concept become importance to be applied in guidance and counseling.